1998
DOI: 10.1007/bf03395268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Response Cost in Computerized Programmed Instruction

Abstract: Punishment improves discrimination learning, and programmed instruction is an elaborate form of discrimination training, so the present experiment assessed whether punishment also improves performance on programmed instruction. The cost of such improvement in terms of increased training time and dissatisfaction of subjects also was assessed. Three college students completed a computerized version of Holland and Skinner's (1961) programmed text. One subject received a two-component multiple schedule within a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
3
15
4
1
Order By: Relevance
“…These results also provide evidence that the effectiveness of time-outs to enhance learning can be extended to tasks that generate relatively little proactive interference across trials. These results are also consistent with the research that has demonstrated that punishers can enhance performance to a greater degree than reinforcers alone (Harris & Tramontana, 1973;Munson & Crosbie, 1998;Penney, 1967;Penney & Lupton, 1961;Stevenson, et al, 1959). The results of the current study coincide with the research showing that punishers of greater magnitude (Camp et al, 1967), including time-outs of longer duration (Ferster & Appel, 1961;Hobbs, Forehand, & Murray, 1978;Zimmerman & Ferster, 1963), are more effective at altering behavior than punishers of lesser magnitude.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results also provide evidence that the effectiveness of time-outs to enhance learning can be extended to tasks that generate relatively little proactive interference across trials. These results are also consistent with the research that has demonstrated that punishers can enhance performance to a greater degree than reinforcers alone (Harris & Tramontana, 1973;Munson & Crosbie, 1998;Penney, 1967;Penney & Lupton, 1961;Stevenson, et al, 1959). The results of the current study coincide with the research showing that punishers of greater magnitude (Camp et al, 1967), including time-outs of longer duration (Ferster & Appel, 1961;Hobbs, Forehand, & Murray, 1978;Zimmerman & Ferster, 1963), are more effective at altering behavior than punishers of lesser magnitude.…”
Section: Discussionsupporting
confidence: 91%
“…Punishment for incorrect responses, combined with reinforcement for correct responses, enhances task performance to a greater degree than when reinforcement for correct responses is used alone (Harris & Tramontana, 1973;Munson & Crosbie, 1998;Penney, 1967;Penney & Lupton, 1961;Stevenson, Weir, & Zigler, 1959). In one study, adults, randomly assigned to one of four groups that differed in the contingencies for correct and incorrect responses, learned a discrimination task (Trent, 1983).…”
mentioning
confidence: 99%
“…In recent years, computer-based instruction has been used to teach a range of skills to normally developing adults. The skills include concepts and principles of behavior analysis (Miller & Malott, 1997;Munson & Crosbie, 1998;Tudor, 1995), use of computer software (Karlsson & Chase, 1996), computer programming commands (Kritch & Bostow, 1998), and programmed instruction design (Tudor & Bostow, 1991). The instructional programs have often been guided by the principles of programmed instruction (Skinner, 1968), which involves segmenting complex skills into their subcomponents, with each component taught to mastery in a series of steps in which prompting is initially provided frequently and then gradually, systematically, and completely faded.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…munson and Crosbie (1998) showed that punishment (5¢ earned for correct, 5¢ lost for incorrect) was better than baseline (5¢ earned for each response). This may be a punishment effect, but it could as easily be a reinforcement effect, given that the 'punishment' condition also involved a reinforcement contingency that was not present in the baseline condition.…”
Section: Extra-instructional Consequencesmentioning
confidence: 99%